Calibration of panoramic cameras with coded targets and a 3D calibration field - Tommaselli, A. M.G. [UNESP]; Marcato, J. [UNESP]; Moraes, M. V.A. [UNESP]; Silva, S. L.A. [UNESP]; Artero, A. O. [UNESP] (Copernicus Publications, 2014)
The aim of this paper is to present results achieved with a 3D terrestrial calibration field, designed for calibrating digital cameras and omnidirectional sensors. This terrestrial calibration field is composed of 139 ARUCO coded targets. Some experiments were performed using a Nikon D3100 digital camera with 8mm Samyang Bower fisheye lens. The camera was calibrated in this terrestrial test field using a conventional bundle adjustment with the Collinearity and mathematical models specially designed for fisheye lenses. The CMC software (Calibration with Multiple Cameras), developed in-house, was used for the calibration trials. This software was modified to use fisheye models to which the Conrady-Brown distortion equations were added. The target identification and image measurements of its four corners were performed automatically with a public software. Several experiments were performed with 16 images and the results were presented and compared. Besides the calibration of fish-eye cameras, the field was designed for calibration of a catadrioptic system and brief informations on the calibration of this unit will be provided in the paper.
Keywords: Automation; Calibration; Close range; Fisheye; Panoramic; Targets